The Question of Modern Economic Development in Greek Historiography and its Public Perception during the 20th century (1907–1990) - Franghiadis, Alexis (Historein, 2018)
Presumed traits of the Greek economy, such as backwardness, dependence, faulty entrepreneurship, shortage of capital and aversion to industrial investment, have long constituted a solid stereotype, which emerged in the 1930s. The stereotype was undermined by empirical research during the first period of intense growth of economic history in Greece, from 1974 to 1990. It continues, however, to be perpetuated, even in academia. Its main components are the historiographical silence on the significance that Greek business networks in the Balkans, the Middle East and southern Russia had for the Greek economy; contempt for the presumably feeble and unreliable Greek bourgeoisie; an extreme reliance on the regulatory role of the state, which permeated the political spectrum; and misapprehension of progress outside the secondary sector. The persistence of the stereotype reduces our ability to analyse actual problems that are related to contradictions inherent in modernity and postmodernity, rather than to backwardness or underdevelopment.